2014
DOI: 10.12694/scpe.v15i2.981
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive time-based coordinated checkpointing for cloud computing workfl ows

Abstract: Abstract. Cloud computing is a new benchmark towards enterprise application development that can facilitate the execution of workflows in business process management system. The workflow technology can manage the business processes efficiently satisfying the requirements of modern enterprises. Besides the scheduling, the fault tolerance is a very important issue in the workflow management. In this paper, we analyse and compare between some existing checkpointing strategies, then we propose a lightweight checkp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 29 publications
(67 reference statements)
1
16
0
Order By: Relevance
“…Meroufel and Belalem [6] proposed an adaptive time-based coordinated checkpointing technique without clock synchronization on the cloud infrastructure. Between the different VMs, jobs can communicate with each other through a messagepassing interface.…”
Section: State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation
“…Meroufel and Belalem [6] proposed an adaptive time-based coordinated checkpointing technique without clock synchronization on the cloud infrastructure. Between the different VMs, jobs can communicate with each other through a messagepassing interface.…”
Section: State Of the Artmentioning
confidence: 99%
“…Logging the messages can also resolve the transit-message problem. The initiator selection is also investigated in Meroufel and Belalems other work [7]; they found that the impact of initiator choice is significant in terms of performance. They also proposed a simple and efficient strategy to select the best initiator.…”
Section: State Of the Artmentioning
confidence: 99%
“…Meroufel and Belalem [9] proposed an adaptive time-based coordinated checkpointing technique without clock synchronization on cloud infrastructure. Between the different VMs jobs can communicate with each other through a message passing interface.…”
Section: A1mentioning
confidence: 99%
“…The authors of [5,6,7,8] make some assumptions or gather statistics about failure distribution of individual resources or resource systems and based on these values and calculations adjust fault tolerant mechanisms. For example Theresa et al propose in their work [8] two dynamic checkpoint strategies: Last Failure time based Checkpoint Adaptation (LFCA) and Mean Failure time based Checkpoint Adaptation (MFCA) which takes into account the stability of the system and the probability of failure concerning the individual resources.…”
Section: A Fault Tolerancementioning
confidence: 99%